Modalidad presencial post pandemia y desarrollo de ansiedad en un adolescente de 13 años del cantón Baba - Macias Murillo, Juan Alberto (2022)
The present case study was carried out with the interest of knowing about the incidence of the post-pandemic face-to-face modality in the development of anxiety in a 13-year-old adolescent from the Baba canton, because returning to face-to-face classes entails various health protocols and physical distancing, which can lead to mental health problems in certain students, such as anxiety, the beneficiary of the case study is the adolescent, the family, the educational unit where the patient studies, and the community university, this case study will remain as a research contribution and it was feasible because it had the authorization of the mother, and the collaboration and availability of the adolescent, and for the collection of information for the case study the following were used: as The type of research used was the correlational and the non-experimental design, the mixed research approach was also used. And the techniques of direct observation and the semi-structured interview and instruments were also used, the clinical history, Hamilton anxiety scale and Liebowitz Scale for social anxiety were used. According to the results obtained, it was possible to determine that the face-to-face modality post-pandemic if it affects the development of adolescent anxiety since it could be denoted that the return to face-to-face classes post-pandemic ends up affecting the adolescent in terms of their emotions, their thoughts, and their behavior, due to all the tension that it generates leaving his house to school where he feels suffocated with all the protocols he must follow, and all this causes him fears, nerves and thoughts that something could happen to him, such as getting infected, which led him to adopt an isolation behavior.